The Effectiveness Of Legal Protection For Prospective Hajj Pilgrims Who Are Victims Of Illegal Visa Use: A Study At The South Sulawesi Provincial Police Department: Efektivitas Perlindungan Hukum bagi Calon Jemaah Haji yang Menjadi Korban Penyalahgunaan Visa: Sebuah Studi di Kepolisian Daerah Sulawesi Selatan - Andi Hamka; La Ode Husen; Azwad Rachmat Hambali; Muhammad Kamran (CV. AFDIFAL MAJU BERKAH, 2026)
This study aims to identify and understand the effectiveness of legal protection for prospective Hajj pilgrims who are victims of illegal visa use within the jurisdiction of the South Sulawesi Regional Police. This study employs an empirical legal research method (socio-legal research) with an empirical juridical approach that emphasizes the application of law in practice (law in action). Data were collected through interviews, questionnaires, and document analysis involving law enforcement officials, relevant agencies, community leaders, and victims. The results indicate that the effectiveness of legal protection is influenced by five factors according to Soerjono Soekanto’s theory: legal factors, law enforcement, infrastructure, society, and culture. All of these factors remain in the “less effective” category, with percentages of 54.11% for legal factors, 52.94% for law enforcement, 56.48% for facilities and infrastructure, 58.82% for society, and 51.77% for culture. This study recommends strengthening inter-agency coordination, improving legal education for the public, enforcing the law firmly and consistently, and optimizing surveillance facilities and technology to prevent the use of illegal visas in the administration of the Hajj